Aloe activated P-glycoprotein and CYP 3A: a study on the serum kinetics of aloe and its interaction with cyclosporine in rats. Issue 1 (23rd December 2016) - Yang, Meng-Syuan; Yu, Chung-Ping; Huang, Ching-Ya; Chao, Pei-Dawn Lee; Lin, Shiuan-Pey; Hou, Yu-Chi
Abstract : Aloe, the leaf juice of Aloe vera, is a popular functional food worldwide. Abstract : Aloe, the leaf juice of Aloe vera, is a popular functional food worldwide. The major constituents of aloe are polyphenolic anthranoids such as aloin, aloe-emodin and rhein. Cyclosporine (CSP), an immunosuppressant with a narrow therapeutic window, is a probe substrate of P-glycoprotein (P-gp), an efflux pump, and CYP 3A4. This study first investigated the serum kinetics of aloe, then evaluated the modulation effects of aloe on P-gp and CYP 3A through an aloe–CSP interaction study in rats. The serum kinetic study showed that aloe-emodin glucuronides (G) and rhein sulfates/glucuronides (S/G) were major molecules in the bloodstream. The aloe–CSP interaction study showed that the systemic exposure to CSP was significantly decreased by either a single dose or multiple doses of aloe. The results of in vitro studies indicated that aloe activated P-gp and aloe metabolites activated CYP 3A4. In conclusion, aloe ingestion activated the functions of P-gp and CYP 3A in rats.